Proceedings of Fatigue, Durability and Fracture Mechanics - Seetharamu, S.; Rao, K. Bhanu Sankara; Khare, Raghunath Wasudev (Lecture Notes in Mechanical Engineering,, 2018)
This book presents the proceedings of Fatigue Durability India 2016, which was held on September 28-30 at J N Tata Auditorium, Indian Institute of Science, Bangalore. This 2nd International Conference & Exhibition brought international industrial experts and academics together on a single platform to facilitate the exchange of ideas and advances in the field of fatigue, durability and fracture mechanics and its applications. This book comprises articles on a broad spectrum of topics from design, engineering, testing and computational evaluation of components and systems for fatigue, durability, and fracture mechanics. The topics covered include interdisciplinary discussions on working aspects related to materials testing, evaluation of damage, nondestructive testing (NDT), failure analysis, finite element modeling (FEM) analysis, fatigue and fracture, processing, performance, and reliability. The contents of this book will appeal not only to academic researchers, but also to design engineers, failure analysts, maintenance engineers, certification personnel, and R&D professionals involved in a wide variety of industries. .